From Feedback to Action: Improving Teaching Through Formative Assessment (Sahayaatra सहयात्रा, 2025)
This study investigates how formative assessment contributes to improving classroom instruction in secondary schools. The primary aim is to understand how teachers and students experience and respond to formative assessment practices and how these practices shape the teaching and learning process. Adopting a qualitative research design, the study draws on data collected through in-depth interviews with teachers and focus group discussions with students, along with classroom observations conducted over two weeks. Using thematic analysis, the research identifies common patterns and insights from participants' experiences. The findings reveal that formative assessment, when used effectively, strengthens the relationship between teaching and learning. Teachers who regularly provide timely feedback, adapt their instruction based on students' needs, and encourage active student participation create more responsive and inclusive classrooms. Students, in turn, become more engaged, better understand learning goals, and feel more confident in their progress. The study also highlights several challenges, such as limited time, lack of training, and inconsistent implementation, which can hinder the full benefits of formative assessment. Overall, the research shows that formative assessment is more than just a tool for measuring learning—it is a process that fosters reflection, dialogue, and growth for both teachers and learners. By integrating these practices thoughtfully, educators can make instruction more effective and support students in achieving deeper understanding and improved outcomes.